Advancements in General and Medical Physics: The Role of Lasers in Modern Healthcare - Khalaf, Shahad Ali Abdulhussein; Aboub, Zahraa Laith Adham; AbisJafar, Mustafa Kazem; abaob, Abdullah laith adham; Radi, Haider Adel Ward (American Journal of Botany and Bioengineering, 2025)
It is widely believed in the general public that the laser plays an important role in modern healthcare, and it is becoming increasingly common among medical professionals as well. For that reason, an investigation of laser web pages on popular science websites will result in articles such as ‘Benefits and risks of using laser therapy for varicose veins’. It is fair to conclude that the presence of laser medical devices in the form of muscle pain relief and tissue health promotion is becoming ubiquitous in the Western world. However, despite this familiarity, the physical principles that make laser use possible remain largely mysterious. This ‘scaling issue’ is made more serious by clinical data that suggest lasers in different wavelengths and pulse entangles have somewhat counterintuitive effects . Given the increased availability of these devices to individual consumers, a thorough campaign of education is warranted. Thus, the goal of this paper is to provide an introduction to the research; how lasers are used in modern medicine, and how they are implemented in medicine. The paper is geared towards a general audience with a background in physics: this includes medical professionals, commercial developers, scientists, and layman with a penchant for understanding new technologies. Regardless, a part is included which aims to quantitative argue how the parameters of a laser affect its effect on the body, even if it necessitates the application of physical principles beyond simple algebra. The semi-technical section endeavours to explain terms that are non-technical.